Lessons from the Rain Forest : Experiences of the Pilot Program to Conserve the Amazon and Atlantic Forests of Brazil - World Bank (Washington, DC, 2012)
The largest hydrographic basin in the world, the Amazon is the source of 20 percent of all the fresh water on the planet. The Basin covers some 600 million hectares in nine countries, over half of which are located within Brazil's national boundaries. A striking characteristic of the Amazon region is its tremendous biodiversity, which includes an estimated 50,000 species of plants, 3,000 species of fish and over 400 known species of mammals. To date, scientists have classified 467 species of reptiles and 516 species of amphibians. Nearly 2,000 known species of birds and the majority of the world's primates are endemic to Amazonia. An estimated 20 million people currently live in the Brazilian Amazon, the majority in urban areas. The region is home to over 170 indigenous groups with distinct cultures, in various levels of contact with the outside world. A variety of social and economic groups are also part of the rural landscape, including rubber-tappers, Brazil nut gatherers, riverine populations, migrant settlers, placer miners, loggers and cattle ranchers. In the 1960s and 1970s, a rapid process of frontier expansion was initiated in the Brazilian Amazon, associated with cattle ranching, commercial logging, and creation of rural settlements, mining, road construction and hydroelectric projects. Over a period of four decades, approximately 78 million hectares in the Brazilian Amazon (15.3 percent of the total area) were cleared. About 70 percent of this deforestation has occurred along the southern flanks of the Amazon, in the states of Para, Mato Grosso and Rondonia.